Karakteristik Organoleptik dari tempe modifikasi dengan kacang kedelai hitam (Glycine max (L) Merrit) - Alfi Rahmawan; Ihsan Jabran Mumtaz; Rera Haiefinah; Lulu Zakiyah Hasna; Elisabeth Michaela Pareira; Rifqi Ahmad Riyanto; Vega Yoesepa Pamela (Litbang PWM Jawa Tengah, 2021)
Tempeh is a fermented food from soybean seeds using the fungus Rhizopus oligosporus. Tempeh is usually made from ordinary fermented soybeans. However, there are various types of beans besides ordinary soybeans, one of which is black soybeans. Food product innovation is closely related to consumer acceptance. Acceptance can be measured using organoleptic test. Organoleptic testing is an important component in the process of making food product innovations. In this study, tempeh was made with a mixture of soybeans and black soybeans in a ratio of 50:50. The resulting tempeh was then tested organoleptically including the parameters of color, texture, aroma, and overall and compared with commercial tempeh on 45 panelists. Based on this research, it is known that the overall parameters, namely color, texture, aroma, and overall in soybean tempeh and 50:50 black soybeans have lower acceptability than commercial tempeh so that further development of these products is needed so that consumer acceptance is higher increase.